Pengaruh E- Commerce dan Promosi di Media Sosial Terhadap Peningkatan Penjualan Produk CV. KBL Interior Bandar Lampung - Indah Wahyuni; Umar Bakti; Evi Meidasari M (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Electronic Commerce or e-commerce is all buying and selling activities or transactions carried out using electronic media (the internet). Even though telephones and television are included as electronic means, e-commerce now refers more to digital technology or the internet. Social media marketing or what is usually called social media marketing is a form of digital marketing that uses social media platforms and network websites with the aim of promoting an organization's products and services through paid or unpaid means. The purpose of this research is to determine the influence of E-commerce and Social Media Promotion on Increasing CV Product Sales. Kbl Interior Bandar Lampung. This research is quantitative research. The research results show that E-commerce (X1) partially has no influence on Sales (Y) and Social Media Promotion (X2) partially has an influence on CV Sales (Y). Kbl Interior Bandar Lampung. Together E-commerce (X1) and Social Media Promotion (X2) have an influence of 48% on CV Sales (Y). Kbl Interior Bandar Lampung, while the remaining 52% was influenced by other factors not studied by researchers.